Permainan Lego dan Kreativitas Anak: A Scoping Review: Lego Play and Children's Creativity: A Scoping Review - Reneta Utami Putri; Abdul Muhid (Universitas Ngudi Waluyo, 2026)
This study is a scoping review aimed at mapping empirical findings regarding the role of Lego play in enhancing the creativity of early childhood (EC) children. Out of 85 identified articles, 23 studies met the inclusion criteria based on the Arksey & O’Malley framework and PRISMA-ScR. The review results indicate that Lego consistently improves children's creativity, especially in aspects of fluency of ideas, flexibility, and originality. Additionally, Lego also contributes to the development of fine motor skills, cognitive abilities, and socio-emotional development through constructive activities and cooperation during play. Although the findings show strong benefits, most studies still have limitations such as small sample sizes, varying creativity instruments, and designs without control groups. Future research is recommended to use more robust designs and standardized instruments. Overall, Lego has proven to be an effective educational medium for stimulating creativity and holistic development in children. ABSTRAK Penelitian ini merupakan scoping review yang bertujuan memetakan temuan empiris mengenai peran permainan Lego dalam meningkatkan kreativitas anak usia dini (AUD). Dari 85 artikel yang diidentifikasi, 23 studi memenuhi kriteria inklusi berdasarkan kerangka Arksey & O’Malley serta PRISMA-ScR. Hasil review menunjukkan bahwa Lego secara konsisten meningkatkan kreativitas anak, terutama pada aspek kelancaran ide, fleksibilitas, dan orisinalitas. Selain itu, Lego juga berkontribusi pada perkembangan motorik halus, kognitif, dan sosial-emosional melalui aktivitas konstruktif dan kerja sama saat bermain. Meskipun temuan menunjukkan manfaat yang kuat, sebagian besar studi masih memiliki keterbatasan berupa ukuran sampel kecil, instrumen kreativitas yang bervariasi, dan desain tanpa kelompok kontrol. Penelitian mendatang direkomendasikan menggunakan desain yang lebih kuat dan instrumen terstandarisasi. Secara keseluruhan, Lego terbukti sebagai media edukatif yang efektif untuk menstimulasi kreativitas dan perkembangan holistik anak